2015
DOI: 10.1002/mrd.22600
|View full text |Cite
|
Sign up to set email alerts
|

Nop2 is required for mammalian preimplantation development

Abstract: SUMMARY Nucleolar protein 2 (NOP2) is evolutionarily conserved from yeast to human, and has been found to play an important role in accelerating cell proliferation, cell-cycle progression, and tumor aggressiveness. The expression pattern and function of Nop2 during early mammalian embryo development, however, has not been investigated. We identified Nop2 as an essential gene for development to the blastocyst stage while performing an RNA interference (RNAi)-based screen in mouse preimplantation embryos. Nop2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
(37 reference statements)
5
26
1
Order By: Relevance
“…S6). Additionally, our previous experiments using dsRNA resistant mRNA22 and different siRNAs targeting separate locations of same mRNA21 also support the specificity of dsRNA mediated RNAi as a screening tool. Importantly, recent reports of gene knockout phenotypes are consistent with our screen induced phenotypes ( Actl6a 65, Bcor 66, Ctr9 53, Gabpa 67, Pbrm1 68, Rtn4 69, Supt6 70 and Ube2a 71).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…S6). Additionally, our previous experiments using dsRNA resistant mRNA22 and different siRNAs targeting separate locations of same mRNA21 also support the specificity of dsRNA mediated RNAi as a screening tool. Importantly, recent reports of gene knockout phenotypes are consistent with our screen induced phenotypes ( Actl6a 65, Bcor 66, Ctr9 53, Gabpa 67, Pbrm1 68, Rtn4 69, Supt6 70 and Ube2a 71).…”
Section: Discussionsupporting
confidence: 64%
“…Under our conditions, control embryos after microinjection and culture show precisely the same morphological and developmental progression as embryos in utero (Fig. 1A) and the rate of blastocyst formation is greater than 90%2122.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…It has been previously shown that NOP2 is localized in the nucleolus in cancer cells . However, immunostaining assay revealed a nonspecific distribution of NOP2 in mouse preimplantation embryos . The discrepancy prompted us to examine the NOP2 localization in early embryos with an alternative antibody (sc‐398884).…”
Section: Resultsmentioning
confidence: 99%
“…Because Gm11545 is specifically expressed in oocytes and preimplantation embryos, it is possible that the protein performs a function unique to embryonic development. To investigate whether Gm11545 is necessary for preimplantation development, we performed knockdown analysis by microinjecting Gm11545-derived dsRNA (dsRNA-Gm11545) into mouse zygotes at the pronuclear stage (21)(22)(23)(24) and confirmed knockdown of the target gene in embryos. Real-time qPCR measurement of mRNA showed that Gm11545 expression is reduced by 76 and 79%, compared with control, at 2-cell and morula stages, respectively (Fig.…”
Section: Impaired Blastocyst Formation In Gm11545 Knockdown Embryosmentioning
confidence: 99%